2009
DOI: 10.1016/j.ppnp.2009.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Status and prospects of top-quark physics

Abstract: The top quark is the heaviest elementary particle observed to date. Its large mass of about 173 GeV/c 2 makes the top quark act differently than other elementary fermions, as it decays before it hadronises, passing its spin information on to its decay products. In addition, the top quark plays an important role in higher-order loop corrections to standard model processes, which makes the top quark mass a crucial parameter for precision tests of the electroweak theory. The top quark is also a powerful probe for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 330 publications
(407 reference statements)
0
19
0
Order By: Relevance
“…In hadron colliders, top-quark production is dominated by the production of tt pairs [1]. At the Tevatron, where the top quark was discovered in 1995 [2,3], tt pairs are predominantly produced through quark-antiquark annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…In hadron colliders, top-quark production is dominated by the production of tt pairs [1]. At the Tevatron, where the top quark was discovered in 1995 [2,3], tt pairs are predominantly produced through quark-antiquark annihilation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of applying these techniques to more than 3 f b −1 of data, both collaborations managed to measure the tt cross section with total uncertainty of about 10% [8]. This is below the theoretical uncertainty.…”
Section: Top Productionmentioning
confidence: 99%
“…The production of single top quarks via electroweak interactions will then be topic of section 2.2.2. Detailed reviews on top-quark physics in hadron collisions can be found in references [37][38][39][40].…”
Section: Top Quarksmentioning
confidence: 99%